2021
DOI: 10.1523/eneuro.0062-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Growth Restriction Causes Abnormal Embryonic Dentate Gyrus Neurogenesis in Mouse Offspring That Leads to Adult Learning and Memory Deficits

Abstract: Human infants who suffer from intrauterine growth restriction (IUGR), which is a failure to attain their genetically predetermined weight, are at increased risk for postnatal learning and memory deficits. Hippocampal dentate gyrus (DG) granule neurons play an important role in memory formation; however, it is unknown whether IUGR affects embryonic DG neurogenesis, which could provide a potential mechanism underlying abnormal postnatal learning and memory function. Using a mouse model of the most common cause o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
31
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 56 publications
7
31
0
Order By: Relevance
“…However, numerous rodent studies using uterine artery ligation or hypoxia exposure of the pregnant dams have established the association between IUGR and impaired cognitive function, recapitulating clinical observations of increased risks of neurodevelopmental impairment among individuals with IUGR and small for gestational age ( Dubrovskaya and Zhuravin, 2010 ; Delcour et al, 2012 ; Sab et al, 2013 ; Howell and Pillai, 2014 ). Similar to our study, a recent study used thromboxane A 2 to induce IUGR in mice and found deficits in hippocampal dentate gyrus neurogenesis as well as in short-term adult learning and memory ( Brown et al, 2021 ).…”
Section: Discussionsupporting
confidence: 89%
“…However, numerous rodent studies using uterine artery ligation or hypoxia exposure of the pregnant dams have established the association between IUGR and impaired cognitive function, recapitulating clinical observations of increased risks of neurodevelopmental impairment among individuals with IUGR and small for gestational age ( Dubrovskaya and Zhuravin, 2010 ; Delcour et al, 2012 ; Sab et al, 2013 ; Howell and Pillai, 2014 ). Similar to our study, a recent study used thromboxane A 2 to induce IUGR in mice and found deficits in hippocampal dentate gyrus neurogenesis as well as in short-term adult learning and memory ( Brown et al, 2021 ).…”
Section: Discussionsupporting
confidence: 89%
“…Following up children with intrauterine growth restriction, most infants and young children will have excessive weight gain, also known as compensatory growth [ 23 ]. Therefore, intrauterine growth restriction is a risk factor for late obesity [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the hippocampus, IUGR produces hypoplasia and reduced number and dendritic complexity of neurons [12-15]. IUGR models that produce a hypertensive-like phenotype in pregnancy mirror these human findings by replicating hippocampal hypoplasia [16] and hippocampal-dependent memory deficits [17-19], which are common in neurodevelopmental disorders and psychopathologies [20, 21]. However, the mechanisms underlying these structural and functional deficits need further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…First, the hippocampus has a well-defined CPd of synaptic plasticity [24, 25, 35-38] improving our ability to interpret our data. Second, hippocampal hypoplasia and dysfunction, as seen in our model [16], have been characterized in patients with IUGR [17] and those with schizophrenia [20, 21]. Thus, studying the molecular alterations in the events governing the hippocampal CPd will improve our ability to make meaningful contributions about the mechanistic origins of neurodevelopmental disorders and psychopathology in IUGR patients.…”
Section: Introductionmentioning
confidence: 99%